Veneers in Prosthodontics: A Comprehensive Review on Evolution, Techniques, and Advancements - Reddy, N Simhachalm; Bekkem, Divya (International Journal of Dental Materials, 2024)
Esthetics in dentistry has become a primary motivation for patients seeking to enhance their smiles, driven by advancements in science and technology. Veneers offer a conservative technique to improve the appearance of teeth, allowing for modifications in shape, size, and colour. Originating from Dr. Charles Pincus's invention in 1928, veneers have significantly evolved, with milestones like Dr. Michael Buonocore's acid etching technique and modern porcelain bonding methods. The design and makeover of a smile encompass facial, dental, and gingival components, ensuring a harmonious and aesthetically pleasing result. Veneers are indicated for various dental issues, including discolouration, enamel cracks, and diastemas, but have contraindications like high caries rate and severe malposition. Recent advances have introduced new materials and techniques, such as lithium disilicate, e.max veneers, and prefabricated composite veneers, enhancing durability and aesthetic outcomes. This review underscores the importance of precise tooth preparation, impression-making, and bonding procedures in achieving successful veneer applications. With continuous innovations, veneers remain a pivotal element in esthetic dentistry, offering patients minimally invasive solutions for a radiant smile.